2019
DOI: 10.1002/vms3.199
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and phenotypic pattern of antibiotic resistance of Acinetobacter baumannii isolated from different types of raw meat samples in Isfahan, Iran

Abstract: Resistant Acinetobacter baumannii isolates are not only known as opportunistic nosocomial bacteria but may also be regarded as emerging bacterial contaminants in foods of animal origins. The present investigation was done to assess the prevalence and antibiotic resistance pattern of A. baumannii isolated from different types of raw meat samples. One hundred and ninety‐four raw meat samples were collected and cultured for A. baumannii isolates. Culture‐positive bacteria were also approved using the loop‐mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Particular attention deserves also cow, sheep, goat, and camel raw meat that can be sources of A. baumannii strains harboring antimicrobial resistance genes for both community and hospital settings environment, posing a potential risk to public health [ 74 ]. Therefore, higher levels of food-related inspection are needed, and further studies are required to define the exact role of this zoonotic pathogen in the food-chain.…”
Section: A Baumannii In Veterinary Medicinementioning
confidence: 99%
“…Particular attention deserves also cow, sheep, goat, and camel raw meat that can be sources of A. baumannii strains harboring antimicrobial resistance genes for both community and hospital settings environment, posing a potential risk to public health [ 74 ]. Therefore, higher levels of food-related inspection are needed, and further studies are required to define the exact role of this zoonotic pathogen in the food-chain.…”
Section: A Baumannii In Veterinary Medicinementioning
confidence: 99%
“… 26 CRAB was detected in 5.8% (3/52) and 11.2% (112/1000) poultry meat in Iran and Turkey, respectively. 45 , 46 In contrast, a study in Switzerland demonstrated that poultry was the most frequently A. baumannii -contaminated type of meat (45.7% of 94 samples); however, none of them were carbapenem resistant. 27 Meat is suspected to be a potential source of MDR A. baumannii , presumably resulting from faecal contamination.…”
Section: Discussionmentioning
confidence: 97%
“…Rare researches have been conducted in this field. Aksari et al [27] reported that the prevalence of A. baumannii in animal species' raw meat was 20.10%. They showed that A. baumannii isolates harbored the higher prevalence of resistance toward azithromycin (66.6%), gentamicin (87.1%), erythromycin (74.3%), tetracycline (79.4%), trimethoprim (56.4%), ciprofloxacin (58.9%), and rifampin (51.2%), which was relatively similar to our findings.…”
Section: Discussionmentioning
confidence: 99%